Chikungunya: From Hypothesis to Evidence of Increased Severe Disease and Fatalities - Carlos Brito; Melissa Barreto Falcão; Maria de Fatima Pessoa Militão de Albuquerque; Thiago Cerqueira-Silva; Maria Glória Teixeira; Rafael Freitas de Oliveira Franca (Viruses)
Chikungunya virus infection often manifests as an acute, self-limiting febrile illness, with arthralgia and musculoskeletal symptoms being the most commonly reported. Arthralgia can persist for months or even years, and approximately 50% of cases progress to chronic conditions. However, recent outbreaks have revealed a rising number of severe cases and fatalities. This review examines evidence from the past decade that suggests a higher incidence of severe chikungunya virus (CHIKV) infections and increased mortality rates, challenging official reports and guidelines from many countries. The literature review includes case reports, series, and studies with comparison groups to assess whether CHIKV-related mortality is underreported. Evaluating excess mortality involves analyzing consistent findings across different regions, biological plausibility, and systemic manifestations that contribute to severe outcomes. These findings aim to expand disease classifications in international guidelines and raise awareness among healthcare professionals to better identify severe CHIKV cases and related deaths. Studies were identified through PubMed using the search terms “chikungunya”, “death”, “severe”, “pathogenesis”, and “pathophysiology”.